Direct displacement-based design as an alternative method for seismic design of bridges - Suarez Chacon, V. (2017)
This paper reviews the Direct Displacement-Based Design Method for seismic design of bridges and compares it to the design procedure implemented in the AASHTO Guide Specification for LRFD Seismic Bridge Design. It is shown with examples that DDBD has several advantages that could be put to use as an alternative design method to that proposed in the AASHTO Guide Specifications for LRFD Seismic Bridge Design.